Inventarisasi Jenis dan Potensi Tumbuhan Marga Elatostema, Pilea, dan Dendrocnide di Hutan Primer Desa Bukum - Zahratul Idami; Melfa Aisyah Hutasuhut; Ike Ramayati (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2022)
Plants of Elatostema, Pilea, and Dendrocnide genus are members of the Urticacea family that are scattered in the forest, one of which is found in the Primery Forest of Bukum Village, Sibolangit. The purpose of this study was to find out what types of plants from the genera Elatostema, Pilea and Dendrocnide live in the Forest of Bukum Village, and identify the potential use of these plants. This research method is an exploratory survey. The plant inventory was obtained using a 10m x 10m plot placed by purposive sampling. While the potential use of the use of research journal literature techniques. The results of this study obtained 8 species of the Elatostema genus, 3 species of the Pilea genus, and 2 species of the Dendrocnide genus. The literature study shows 5 potential uses of each type of plant studied from the three genera of the Urticacea family, namely wood producers, medicinal plants, fruits, vegetable producers, and animal feed